Generation of Persister Cells of Pseudomonas aeruginosa and Staphylococcus aureus by Chemical Treatment and Evaluation of Their Susceptibility to Membrane-Targeting Agents - Grassi, Lucia; Di Luca, Mariagrazia; Maisetta, Giuseppantonio; Rinaldi, Andrea C.; Esin, Semih; Trampuz, Andrej; Batoni, Giovanna (Frontiers in Microbiology, 2017)
Persister cells (PCs) are a subset of dormant, phenotypic variants of regular bacteria, highly tolerant to antibiotics. Generation of PCs in vivo may account for the recalcitrance of most chronic infections to antimicrobial treatment and demands for the identification of new antimicrobial agents able to target such cells. The present study explored the possibility to obtain in vitro PCs of Pseudomonas aeruginosa and Staphylococcus aureus at high efficiency through chemical treatment, and to test their susceptibility to structurally different antimicrobial peptides (AMPs) and two clinically used peptide-based antibiotics, colistin and daptomycin. The main mechanism of action of these molecules (i.e. membrane-perturbing activity) renders them potential candidates to act against dormant cells. Exposure of stationary-phase cultures to optimized concentrations of the uncoupling agent cyanide m-chlorophenylhydrazone (CCCP) was able to generate at high efficiency PCs exhibiting an antibiotic-tolerant phenotype towards different classes of antibiotics. The metabolic profile of CCCP-treated bacteria was investigated by monitoring bacterial heat production through isothermal microcalorimetry and by evaluating oxidoreductase activity by flow cytometry. CCCP-pretreated bacteria of both bacterial species underwent a substantial decrease in heat production and oxidoreductase activity, as compared to the untreated controls. After CCCP removal, induced persisters showed a delay in heat production that correlated with a lag phase before resumption of normal growth. The metabolic reactivation of bacteria coincided with their reversion to an antibiotic-sensitive phenotype. Interestingly, PCs generated by CCCP treatment resulted highly sensitive to three different membrane-targeting AMPs at levels comparable to those of CCCP-untreated bacteria. Colistin was also highly active against PCs of P. aeruginosa, while daptomycin killed PCs of S. aureus only at concentrations 32 to 64-fold higher than those of the tested AMPs. In conclusion, CCCP treatment was demonstrated to be a suitable method to generate in vitro PCs of medically important bacterial species at high efficiency. Importantly, unlike conventional antibiotics, structurally different AMPs were able to eradicate PCs suggesting that such molecules might represent valid templates for the development of new antimicrobials active against persisters.